1969
DOI: 10.1002/cber.19691020430
|View full text |Cite
|
Sign up to set email alerts
|

Zur Chemie des Indols, VI. α.β′‐Diindolylmethane und ‐methene. Der Urorosein‐Chromophor

Abstract: Urorosein entsteht durch Polykondensation von Indolyl‐(3)‐glykolsäure und anschließende Oxydation, wobei sich der α.β′‐Diindolylmethen‐Chromophor bildet. α.β′‐Diindolylmethen (1–5) werden durch Reaktion von α‐freien und β‐freien Indolen mit Glyoxylsäure, α.β′‐Diindolymethene (10–12) aus α‐Formyl‐indolen mit β‐freien Indolen gewonnen. Oxo‐β.β′‐ (13–16) und Oxo‐α.β′‐diindolylmethene (17–20) entstehen aus β‐bzw. α‐Formyl‐indolen mit Oxindolen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The protruding carbonyl groups have an assistance in planarizing the neighboring thiophene units through short contact oxygen−hydrogen interactions. 12,13 Recently, another molecule, isoindigo, which also has two conjugated lactam rings, has attracted close attention and shown promising appliations for photovoltaic cells and OFETs. 14−18 Isoindigo is a symmetrical molecule consisting of two indolin-2-one units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protruding carbonyl groups have an assistance in planarizing the neighboring thiophene units through short contact oxygen−hydrogen interactions. 12,13 Recently, another molecule, isoindigo, which also has two conjugated lactam rings, has attracted close attention and shown promising appliations for photovoltaic cells and OFETs. 14−18 Isoindigo is a symmetrical molecule consisting of two indolin-2-one units.…”
Section: Introductionmentioning
confidence: 99%
“…Organic semiconductors have been studied extensively to develop their potential applications in flexible and low-cost organic opto-electronic devices, such as organic light-emitting diodes, organic photovoltaic cells, and organic field-effect transistors (OFETs). Among all organic semiconductors for OFETs, 1,4-diketo-3,6-dithienylpyrrolo[3,4- c ]pyrrole (DPP) based materials have received tremendous attention for their promising performance. DPP exhibits a planar skeleton with two conjugated lactam rings in couple with two thiophene rings. The protruding carbonyl groups have an assistance in planarizing the neighboring thiophene units through short contact oxygen–hydrogen interactions. , Recently, another molecule, isoindigo, which also has two conjugated lactam rings, has attracted close attention and shown promising appliations for photovoltaic cells and OFETs. Isoindigo is a symmetrical molecule consisting of two indolin-2-one units. Crystallographic studies on alkyl-substituted isoindigo show that the central carbon–carbon double bond exhibits an E configuration and the two indole heterocycles form a perfect planar π-conjugated structure.…”
Section: Introductionmentioning
confidence: 99%
“…Later we found that analogous compounds showed antitumor activity too. In our first paper on 3-(2-chloro-3-indolylmethylene)1,3-dihydroindol-2-ones as antitumor agents,4 we acknowledged that the first synthesis of the unsubstituted 3-indolylmethylene-1,3-dihydroindol-2-one was performed by a German team in 19695 and the first attempt to search an antitumor potential in this class of compounds was made in 1977 6. We also reported that a team at Farmitalia-Carlo Erba was working on the antitumor activity of analog compounds 7.…”
Section: Introductionmentioning
confidence: 99%
“…Th‐DPP exhibits a planar skeleton with two conjugated lactam rings in coupled to two thiophene rings. The protruding carbonyl units assist in the planarization of adjacent thiophene units through short contact oxygen–sulfur interactions, which will increase the degree of back bone coplanarity (Figure S1, Supporting Information) . Recently, indigo (IDG), isoindigo (IIDG), and their derivative chromophore were also recognized as potential building blocks similar to Th‐DPP; exhibiting excellent performances (Figure S1, Supporting Information) .…”
Section: Introductionmentioning
confidence: 99%